The adapted lifestyle-integrated functional exercise program for preventing functional decline in young seniors: development and initial evaluation - Schwenk, Michael; Bergquist, Ronny; Boulton, Elisabeth; Van Ancum, Jeanine M.; Nerz, Corinna; Weber, Michaela; Barz, Carolin; Jonkman, Nini H.; Taraldsen, Kristin; Helbostad, Jorunn L.; Vereijken, Beatrix; Pijnappels, Mirjam; et al. (Gerontology, 2019)
Background: The Lifestyle-integrated Functional Exercise (LiFE) program is an intervention integrating balance and strength activities into daily life, effective at reducing falls in at-risk people ≥70 years. There is potential for LiFE to be adapted to young seniors in order to prevent age-related functional decline. Objective: We aimed to (1) develop an intervention by adapting Lifestyle-integrated Functional Exercise (aLiFE) to be more challenging and suitable for preventing functional decline in young seniors in their 60s and (2) perform an initial feasibility evaluation of the program. Pre-post changes in balance, mobility, and physical activity (PA) were also explored. Methods: Based on a conceptual framework, a multidisciplinary expert group developed an initial aLiFE version, including activities for improving strength, neuromotor performances, and PA. Proof-of-concept was evaluated in a 4-week pre-post intervention study measuring (1) feasibility including adherence, frequency of practice, adverse events, acceptability (i.e., perceived helpfulness, adaptability, level of difficulty of single activities), and safety, and (2) changes in balance/mobility (Community Balance and Mobility Scale) and PA (1 week activity monitoring). The program was refined based on the study results. Results: To test the initial aLiFE version, 31 young seniors were enrolled and 30 completed the study (mean age 66.4 ± 2.7 years, 60% women). Of a maximum possible 16 activities, participants implemented on average 12.1 ± 1.8 activities during the intervention, corresponding to mean adherence of 76%. Implemented activities were practiced 3.6-6.1 days/week and 1.8-7.8 times/day, depending on the activity type. One noninjurious fall occurred during practice, although the participant continued the intervention. The majority found the activities helpful, adaptable to individual lifestyle, appropriately difficult, and safe. CMBS score increased with medium effect size (d = 0.72, p = 0.001). Increase in daily walking time (d = 0.36) and decrease in sedentary time (d = -0.10) were nonsignificant. Refinements included further increasing the task challenge of some strength activities and defining the most preferred activities in the trainer’s manual to facilitate uptake of the program. Conclusion: aLiFE has the potential to engage young seniors in regular lifestyle-integrated activities. Effectiveness needs to be evaluated in a randomized controlled trial.
Gesehen am 16.04.2020